The impact of park surface substrates on atmospheric temperature: a quantitative analysis based on remote sensing technology and CFD simulation - Xian, Ning; Chen, Hao (Proceedings of SPIE, the international society for optical engineering, 2025)
The study takes Chang Le Park, Xing Qinggong Park, and Revolutionary Park in Xi'an as the research subjects, using the Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), and Normalized Difference Water Index (NDWI) to calculate the composition and characteristics of the park's underlying surface elements. The study utilizes ENVI-met for simulating the thermal environment of the parks and performs a multiple linear regression analysis to evaluate the influence of the park's underlying surface on atmospheric temperature. The research indicates that for every 1% increase in vegetation coverage, the temperature decreases by 0.4°C, while for every additional hectare of park area, the temperature decreases by 0.006°C. This study quantitatively reveals the regulatory effect of park surfaces on temperature and provides a scientific basis for urban planning and green space design.